Scaling-up continuous production of mesoporous silica particles at kg scale: design & operational strategies - Jundale, Rajashri B.; Sonawane, Jayesh R.; Palghadmal, Anil V.; Jaiswal, Hemant Kumar; Deore, Hital S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2024)
This paper demonstrates a continuous flow pilot-scale production of highly porous mesoporous silica particles (MSPs) via a soft template based technique. The study presents pilot scale reactor design, fabrication and production of mesoporous silica particles with a 1 kg per day production rate. The extent of mixing and overall performance of the system were evaluated by conducting a hydrodynamic study, including the estimation of the heat transfer coefficient and dispersion number. Nanoparticle synthesis in a clogging-free manner is the key challenge in moving towards large scale production and commercial applications. This article presents a comprehensive study on the effect of key parameters for successful scaling up of the process. We have also addressed challenges faced and how these are overcome by troubleshooting the process. Different strategies were used to prevent the clogging of the reactor, which involved reactant dilution, periodic pulsation and slug flow (two phase flow). Among them, slug flow allows us to operate the reactor continuously for several hours without clogging and wall-deposition problems. It helped produce morphologically well-defined and near-monodisperse particles. With this process, the production is validated at a scale of 85 times compared to that of a laboratory system (from 22 mL to >1.5 L), enabling a production rate of 20-50 g h(-1).